Spike and block reach of the master Volleyball during the match according to the classification - Marques Junior, Nelson Kautzner (2019)
The attack is the most important skill for the volleyball team gets the win and the block is the second most important volleyball skill. The objective of the study was to determine the spike and the block reach of the master volleyball according to the classification. The study was composed by 15 matches of the male master volleyball of the category 35 years or more. The data were collected with the camera in a gymnasium. After of the data collect, the researcher practiced physical performance (spike and block reach) analysis with the Kinovea® software. The volleyball team 3rd to last place had during the match a spike and block reach lower than the 1st and 2nd place, but the study did not identify statistical difference of this comparison. The team 3rd to last place had during each set a spike and block reach lower than the 1st and 2nd place. The significance p and the new statistic detected statistical difference of each set of the spike reach in five comparisons and of the block reach in two comparisons. In conclusion, the best reach of the spike and of the block is a motive of the better performance of the volleyball team 1st and 2nd place.